Blockchain in fifth-generation network and beyond: a survey - Ahmed Shamil Mustafa; Mohammad Abdulrahman Al-Mashhadani; Salah Ayad Jasim; Ahmed Muhi Shantaf; Mustafa Maad Hamdi (Bulletin of Electrical Engineering and Informatics, 2022)
Fifth-generation (5G) technologies enable a wide range of vertical applications by connecting heterogeneous equipment and machines, resulting in significantly improved service quality, increased network capacity, and improved system performance. As a result, the world is shifting to 5G wireless networks. Because 5G has the advantage of supporting various vertical applications, 5G systems must still overcome challenges such as transparency, data interoperability probabilities, decentralization, and network privacy. In this paper, we'll show how blockchain can be used to solve problems in 5G, as well as some of the idea’s researchers, have come up with to solve them, like resource sharing, security, and mobility.